Use of Vegetation Cover Index (ICV) to identify susceptible areas to desertification process in the semiarid municipalities of Pernambuco, Brazil - Alves, Rayanna Barroso de Oliveira; Silva, Hernande Pereira da; Filho, José Coelho de Araújo; Domingues, Marco Antonio de Oliveira; Albuquerque, Jones Oliveira de (International Journal of Advanced Engineering Research and Science, 2020)
Climate change in Brazil has led to an increase in temperature and changes in the distribution of climatic extremes, such as droughts and floods. This is potentialized when it comes to the brasilian semi-arid Northeast. Environmental studies related to this theme are in constant development. For this, the geotechnologies are of great importance for the environmental studies, since they allow the acquisition and analysis of information of use of the ground, vegetal cover and phenomena of the nature. In the present work, the Vegetation Cover Index was studied using remote sensing and geoprocessing techniques through the digital processing of images acquired in the years 2000 to 2015 of the LANDSAT satellites of three municipalities of Pernambuco to observe the vegetation cover in the said temporal space with the degraded areas possibly resulting from the desertification process in the region. Thus, it was found that the municipalities of Betânia and Itacuruba have very high vulnerability (0.75 and 1, respectively). On the other hand, the municipality of Floresta presented a high vulnerability of ICV (0.5), as the vegetation deficit influences hydrological dynamics, soil protection, climatic stability and thermal influence, corroborating the desertification process.